2012
DOI: 10.1177/039463201202500312
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Micrometric Liposomes as Drug Delivery Systems in the Treatment and Periodontitis

Abstract: Periodontitis is a complex disease and bacterial infection is one of the most common factors involved in this disease. Current strategies for the local delivery of antibiotics do not allow a complete clearance of bacteria filling dentinal tubules and this limits their therapeutic efficacy. Therefore, there is a strong need for the development of new delivery strategies aimed at improving the efficacy of antibiotic therapy for periodontitis with special reference to their ability to penetrate into the tubules. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Di Turp et al have developed liposome-based delivery systems of submicron dimensions which can diffuse into the dentinal tubules [ 107 ]. The liposomes were prepared by hydration of a lyophilized preliposomal formulation consisting of the following components are l- α-phosphatidylcholine β-oleoyl-γ-palmitoyl (POPC), l -α-phosphatidylcholine– d,l -glycerol dioleoyl (PGDO) and cholesterol (CHOL).…”
Section: Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Di Turp et al have developed liposome-based delivery systems of submicron dimensions which can diffuse into the dentinal tubules [ 107 ]. The liposomes were prepared by hydration of a lyophilized preliposomal formulation consisting of the following components are l- α-phosphatidylcholine β-oleoyl-γ-palmitoyl (POPC), l -α-phosphatidylcholine– d,l -glycerol dioleoyl (PGDO) and cholesterol (CHOL).…”
Section: Liposomesmentioning
confidence: 99%
“…Di Turp et al have developed liposome-based delivery systems of submicron dimensions which can diffuse into the dentinal tubules [107].…”
Section: Liposomesmentioning
confidence: 99%
“…Meanwhile, they have lower risks of undesirable side effects, superior efficacy and enhanced patient compliance [7]. Due to the relatively low price, higher stability, nontoxicity, biocompatibility, nonimmunogenicity and biodegradability, a variety of polymers are investigated as drug carriers in various formulations and forms such as fibers [38,39,40,41], strips [42], films [43,44], gels [45,46], micro-particles [47,48,49], nanoparticles [11,50,51,52], and vesicular system [53,54]. Table 1 shows various polymer-based local drug delivery systems delivering a variety of antibiotics, such as metronidazole, doxycycline, tetracycline and secnidazole, for combating periodontal pathogens.…”
Section: Polymeric Materials As Drug Carrier For Combating Periodomentioning
confidence: 99%
“…It was observed that submicrometer magnetized vesicles, subjected to an external magnetic field, were more able to penetrate the tubules since the magnetic field accelerated their movement inside the tubules. Thus this device can provide better clearance of the bacteria from even the deep sites in case of periodontitis (Di Turi et al, 2011). In a recent study Liu and coworkers checked the efficacy of liposome controlledrelease gel containing 2% minocycline hydrochloride in rat periodontitis model.…”
Section: Liposomesmentioning
confidence: 99%